Pulmonary arteriovenous malformation causing lung sequestration and media infarction: a case report - Griffo, Raffaella; Klotz, Laura V.; Brendel, Lena; Rösch, Romina; Niedermaier, Benedikt; Schlamp, Kai; Kriegsmann, Mark; Eichhorn, Martin M.; Winter, Hauke (Frontiers in Medicine, 2025)
Pulmonary arteriovenous malformations (PAVMs) are rare vascular malformations of the lungs. Direct communication of pulmonary arteries to pulmonary veins is the defining characteristic allowing venous blood to bypass the pulmonary capillary system and avoiding an efficient oxygenation process. The complexity of the pathology lies not only in the variety of its manifestations, but also in the choice of the most appropriate and effective treatment. We present a case of a complex PAVM associated with a persistent foramen ovale, with stroke as the onset symptom. Despite timely multidisciplinary treatment of the malformation, a potentially fatal pulmonary complication occurred, highlighting the critical importance of early, interdisciplinary management and ongoing follow-up of PAVMs, particularly in preventing life-threatening outcomes.